FAKTORÃ¢â¬âFAKTOR YANG MEMPENGARUHI KESULITAN BELAJAR AKUNTANSI - Khafid, Muhammad (Dinamika Pendidikan, 2007)
The objective of this study is to know the factors thatÃÂ  influence difficulty in learning accounting. The population were all XII IPS students, MA Al-Asror Gunungpati, Semarang. The sum were 83 students, therefore the population would be the sample of the study. Variables of the study consist ofÃÂ  internal factors (X1) included health condition, interest, motivation and learning habit, and external factors (X2) included school, family, and society factors as the independent variables and difficulty in learning accounting (Y) as the dependent variable.ÃÂ  Data was taken by questionnaire and analyzed by percentage descriptive and regression analysis. Result of the study showed that internal and external factors can influence the difficulty in learning accounting for XII IPS students MA Al-Asror Gunungpati Semarang. Based on the conclusion above, it is suggested that teachers attempt to improve interest and motivation and also to change the learning strategies as suggested in curriculum such as Contextual Learning and Teaching, Jigsaw Method, Thing Pair Share and Student Teaching Active Discussion that appropriate to the characteristics of Accounting subject that emphasizing Students-Center Learning. Keywords : difficulty factors in learning accounting